2009
DOI: 10.1016/j.joca.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Location specific radiographic joint space width for osteoarthritis progression

Abstract: Summary Objective To establish the performance of location specific computer measures of radiographic joint space width (JSW) compared to measurements of minimum joint space width (mJSW) for the assessment of medial compartment knee osteoarthritis (OA). The study also investigated the most disease-responsive location for measuring medial compartment JSW. Methods Serial bilateral Posterior Anterior (PA) conventional radiographs acquired with a fixed flexion protocol were obtained 36 months apart in 118 perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 18 publications
8
92
1
Order By: Relevance
“…1). Based upon superior responsiveness from prior analyses we selected the JSWx ¼ 0.225 as the preferred location for the fixed coordinate JSW measure 25 .…”
Section: X-ray Acquisition and Measurementmentioning
confidence: 99%
“…1). Based upon superior responsiveness from prior analyses we selected the JSWx ¼ 0.225 as the preferred location for the fixed coordinate JSW measure 25 .…”
Section: X-ray Acquisition and Measurementmentioning
confidence: 99%
“…The FTA measurement was defined using a coordinate system to identify the distal aspect of the femoral condyles based on anatomical landmarks for establishing a location-specific joint space width measurement (Fig. 2) [13,14]. Using the largest prominence of the medial and lateral femoral condyles, two lines were identified perpendicular to a tangent at the distal aspect of the condyles.…”
Section: Methodsmentioning
confidence: 99%
“…However, a novel, highly automated method for measuring FTA was recently presented by Iranpour-Boroujeni et al [12] and alignment data obtained with this method are now available for most of the osteoarthritis initiative (OAI) cohort. This method does not define FTA by the shaft but utilizes more local information around the joint space and femoral condyles [12][13][14]. The authors reported greater intra-rater and inter-rater reliability [12] for measuring FTA than the traditional method in participants with knee OA, and somewhat greater correlation with HKA (r ¼ 0.75) than for the traditional FTA measurements (r ¼ 0.68).…”
Section: Introductionmentioning
confidence: 99%
“…1.6, from which quantitative data were obtained, and Right knee symptom status, from which the predicted variable, chronic pain, was obtained. This information was pre analyzed by a radiologist group associated to the OAI using the OARSI quantitative grading scale [28,29][30-32].…”
Section: Methodsmentioning
confidence: 99%